Purification of Human Brain Tissue Factor - Kang, Sungzong; Niemetz, Julian (Thrombosis and Haemostasis, 1988)
Tissue factor (thromboplastin or Factor III), a glycoprotein cofactor, is required for Factor VII to express its catalytic activity, thereby initiating the extrinsic as well as intrinsic pathway of blood coagulation. Human brain tissue factor was purified 2,500-fold to 98% homogeneity from 2% Tiiton X-100 extraction of acetone dried brain powder with an overall yield of 36%. The method was based upon affinity chromatography utilizing the high affinity binding of tissue factor to Factor VII noncovalently complexed to immobilized anti-Factor VII-agarose beads. The apparent molecular weight of the purified tissue factor is 45,000 as judged by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and its isoelectric point is 4.8–5.1 by column chromatofocussing and flat bed agarose isoelectric focussing.
Keywords: Tissue factor; Coagulation; Human brain